Traumatic brain injury and VA service use among Native Hawaiian and Pacific Islander Veterans experiencing homelessness - Holliday, Ryan; Monteith, Lindsey; Liu, Shawn; Lum, Sara; Sia, Marissa; Iwamasa, Gayle; Aase, Darrin; Smith, Alexandra; Deka, Rishi; Jordan, Shiloh; Kindler, Christine; Tsai, Jack; et al. (Frontiers in Public Health, 2025)
IntroductionUnited States Veterans experiencing homelessness often have myriad health concerns that can impact their functioning. Native Hawaiian or Pacific Islander (NHPI) homeless Veterans are up to 82% more likely to have a traumatic brain injury (TBI) diagnosis than non-NHPI homeless Veterans, which can further impact these Veterans’ psychosocial functioning. The Department of Veterans Affairs (VA) offers services to address the health and social needs of these Veterans.MethodsWe examined VA electronic medical record data from 12,205 NHPI Veterans identified as homeless from 1/2005–7/2024. We calculated VA service use (i.e., homeless, justice, emergency, primary care, rehabilitative, mental health, and all other VA service settings) among NHPI homeless Veterans using Veteran electronic medical record data.ResultsAfter accounting for sex, age, and VA service-connected disability, NHPI homeless Veterans with a documented TBI diagnosis were significantly more likely to access and use VA services across service settings.DiscussionNHPI homeless Veterans with TBI histories likely access various types of VA services; as such, wraparound care (e.g., Homeless Patient Aligned Care Teams; case management) are critical for managing care needs. Future research should examine factors that facilitate engagement in and benefit from VA health and social services among these Veterans.